2014
DOI: 10.12785/amis/080126
|View full text |Cite
|
Sign up to set email alerts
|

Soret and Dufour Effects on Peristaltic Transport of MHD Fluid with Variable Viscosity

Abstract: Abstract:This article looks at the Soret and Dufour effects on the magnetohydrodynamic (MHD) peristaltic flow of variable viscosity fluid in a symmetric channel. Analysis is presented in the presence of Ohmic heating. Results for the stream function, temperature and concentration are constructed. The variations of sundry parameters are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Abbasi et al [17] reported the Soret and Dufour effects on peristaltic transport of magneto hydrodynamic fluid with variable viscosity and found that an increase in Soret number reduces the concentration profiles.The effect of thermo diffusion on chemically reacting dusty viscous flow was studied by Reddy et al [18]. In that paper, it is found that increasing values of Soret number enhances the fluid velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Abbasi et al [17] reported the Soret and Dufour effects on peristaltic transport of magneto hydrodynamic fluid with variable viscosity and found that an increase in Soret number reduces the concentration profiles.The effect of thermo diffusion on chemically reacting dusty viscous flow was studied by Reddy et al [18]. In that paper, it is found that increasing values of Soret number enhances the fluid velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Sud et al [25] explored the effect of a moving magnetic field on blood flow. Further, Abbasi et al [26] developed a mathematical model of peristaltic transport of MHD fluid by considering Entropy 2016, 18, 117 3 of 16 variable viscosity. Some relevant studies to magnetic field models can be found from the list of references [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Common examples of pseudoplastic fluids are ketchup, nail polish, molasses, whipped cream, latex paint, some silicone, oils, blood, some silicone coatings, etc. The peristaltic flow of pseudoplastic fluid in a curved channel under the influence of radial magnetic field has been inquiry by Hayat et al [14].Recently, Hayat et al [6] Further the peristalsis subject to magnetic field effects are significant in magnetotherapy, hyperthermia, arterial flow, cancer therapy, etc. The controlled application of low intensity and frequency pulsating fields modify the cell and tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Peristaltic transport of fourth grade fluid with convective conditions is numerically discussed by Mustafa et al [11]. An effect of variable viscosity on peristalsis in the presence of magnetic field is studied by Abbasi et al [6].Kothandapani and Prakash [2] studied the combined effects of radiation and magnetic field on peristaltic transport of nanofluid. The studies related to peristalsis with heat and mass transfer for Newtonian fluid have been structured in ref.…”
Section: Introductionmentioning
confidence: 99%